The Effect of Tax Havens on Host Country Welfare - Thomas Gresik; Dirk Schindler; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2015)
Multinational corporations can shift income into low-tax countries through transfer pricing and debt financing. While most developed countries use thin capitalization rules to limit the extent to which a subsidiary can be financed with internal debt, a number of developing countries do not. In this paper, we analyze the effect on FDI and host country welfare of thin capitalization rules when multinationals can also shift income via transfer prices. We show that while permissive thin capitalization limits may be needed in developing countries to attract FDI, the amount of debt financing allowed by the permissive limits facilitates more aggressive transfer pricing and results in lower host country welfare.
Keywords: D69; 330; multinationals; profit shifting; foreign direct investments; welfare